SETHE'S MERCY KILLING IN MORRISON'S 'BELOVED' - Rina Husnaini Febriyanti (UIN Raden Mas Said Surakarta, 2016)
The aim of this research study is to describe the causes of Sethe’s doing Mercy Killing. The objects of the study are words, phrases, clauses and sentences taken from the novel. The data are collected by the process of recording in cards and tables. The instrument of the research is the researcher herself. The method used in this research study is qualitative method in which the reliability and validity is acquired by expert judgment. The findings of the study show that Sethe’s doing Mercy Killing are caused by the disharmony problems of the id, ego and superego in Sethe’s personality. This study reveals that finally Sethe’s superego controls her personality which leads her to kill her baby. Sethe’s mercy killing happens because she was an exslave woman, she was an African American woman, Sethe wished her daughter in a better place than her, and she hoped her daughter who had been killed by her getting a freedom forever.